2005
DOI: 10.1373/clinchem.2005.049429
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Throughput Automated Analyzer Using Biochip Array Technology

Abstract: Background: Use of protein array technology over conventional assay methods has advantages that include simultaneous detection of multiple analytes, reduction in sample and reagent volumes, and high output of test results. The susceptibility of ligands to denaturation, however, has impeded production of a stable, reproducible biochip platform, limiting most array assays to manual or, at most, semiautomated processing techniques. Such limitations may be overcome by novel biochip fabrication procedures. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(91 citation statements)
references
References 15 publications
1
87
0
2
Order By: Relevance
“…This study builds on previous work by using a validated analytical platform for cytokine measurements and reference ranges for IL-8 and MCP-1 for classifying elevations (9,13 ). Moreover, the cutoffs used in this study closely resemble other reported values in the literature for risk stratification for IL-6 (26 ) and the median value for NT-proBNP in an ACS population (34 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This study builds on previous work by using a validated analytical platform for cytokine measurements and reference ranges for IL-8 and MCP-1 for classifying elevations (9,13 ). Moreover, the cutoffs used in this study closely resemble other reported values in the literature for risk stratification for IL-6 (26 ) and the median value for NT-proBNP in an ACS population (34 ).…”
Section: Discussionsupporting
confidence: 52%
“…In 2006, the EDTA specimens were thawed for the 1st time, and a cytokine array was measured using the evidence investigator™ (Randox) biochip platform (9,13 ). The biochip can assay 12 cytokines; however, a priori the decision was made to evaluate only IL-6, IL-8, and MCP-1 for the present study assessing HF and death in an ACS population.…”
Section: Biomarker Measurementsmentioning
confidence: 99%
“…Although this fundamental phenomenon has been studied for a long time, droplet impact and deformation is still an active field of research due to countless applications and the addition of various novel applications. Study of the droplet impact and deformation process for optimization and better manufacturing accuracy is required for state-ofthe-art processes, including three-dimensional (3D) cell patterning for tissue engineering (Derby, 2008;Moon et al, 2010), hybrid biological-electronic device construction, and biochip-array fabrication (FitzGerald, Lamont, McConnell, & Benchikhel, 2001), as well as traditional manufacturing (e.g., high temperature surfaces with water spray for steel making). Material jetting is one of the manufacturing technologies where the extensive study of droplet formation, dispensing, impact and deformation is essential, as the process is designed to produce a continuous or dropon-demand droplet at a high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This has implications with regards a reduction in sample/reagent consumption and as such the overall cost-effectiveness of assays. Applications of this methodology to protein and drug analysis have been previously described (20)(21)(22)(23)(24). The core of this technology is the biochip (9mm x 9mm), which represents not only the solid support, but also the vessel were hybridisation occurs.…”
mentioning
confidence: 99%